Reconstruction of Customary Law (Adat Law) in Environmental Law Enforcement in Indonesia: A Literature Study from Global and Local Perspectives - Darisera, Stiadi Ivanto; Letedara, Reindino; Latue, Philia Christi; Rakuasa, Heinrich (Rechtsvinding, 2024)
This research explores the intersection of customary law and environmental law enforcement in Indonesia, addressing the significant environmental challenges the country faces, such as deforestation and climate change. Utilizing a literature study methodology, the research analyzes various scientific articles, legal documents, and case studies to identify key themes, challenges, and opportunities related to the integration of customary practices into formal legal frameworks. The results indicate that while customary law has been effective in managing natural resources sustainably, its recognition within the national legal system is often inconsistent, leading to conflicts and undermining indigenous rights. The discussion emphasizes the importance of legal pluralism and the need for greater collaboration between indigenous communities and government authorities. Ultimately, the research concludes that embracing customary law can enhance Indonesia's environmental governance, promote sustainable resource management, and empower local communities, thereby contributing to broader conservation efforts.